Community-Acquired and Nosocomial Pneumonia: Clinical and Morphological Features - A. M. Golubev; T. V. Smelaya; V. V. Moroz; A. A. Popov; A. A. Tolbatov; S. V. Medunetskaya (Общая реаниматология)
Objective: to reveal the clinical and morphological features of acute community-acquired and nosocomial pneumonia (NP). Materials and methods. The results of treatment were retrospectively assessed and those of autoptic studies were analyzed in 43 dead patients with pneumonia. There were two groups: 1) 13 subjects with community-acquired pneumonia; 2) 30 subjects with NP. Results. A clinicomorphological study revealed different stages of acute respiratory distress syndrome (ARDS) in both groups. The probability of its development increases if microbial associations are identified as an etiological factor. In community-acquired pneumonia, ARDS was detected in 6 of the 13 cases in which 5 (83.3%) cases were in the presence of progressive pulmonary inflammation. In Group 2, ARDS was recorded in 21 of the 30 cases and it followed the occurrence of pneumonic infiltration. On days 2 and 3 of ARDS, there were hyaline membranes and a preponderance of interstitial edema. Five days later, inflammatory changes were prevalent, severe alveolar edema (subtotal and total) and multiple hemorrhages were noted, and the number of hyaline membranes increased. Conclusion: The analysis has indicated that ARDS, including acute pulmonary lesion, as the first stage of respiratory distress syndrome in patients with pneumonia of varying genesis is more frequently detectable than traditionally thought. Acute respiratory failure in 27 (62.8%) of the 43 patients was caused by different stages of ARDS, which alone or in combination with other complications was as a cause of death. Key words: acute community-acquired pneumonia, nosocomial pneumonia, respiratory distress syndrome.